Traceability in Food Supply Chains, A Multiple Case Study of Chocolate Producers Using Origin Labelling - Granberg, Sandra; Högberg, Anna (My University, 2015)
Over the past decades, environmental and social issues have become an increasingly growing global concern and simultaneously the environment in which companies operate has changed. Today, it is not enough for companies to take responsibility for their own in-house activities. Rather, they are held responsible for the social and environmental impact of their entire supply chain. Therefore, companies need to work with sustainability throughout their supply chain. However, this is easier said than done, since there is often little traceability in today’s complex multinational supply chains. Still, there are companies that are able to trace components back to their origin, and thus have insight in the structure of their supply chains. Two such companies are the chocolate producers Domori and Belyzium. They label their products with the origin of the cocoa that their chocolate contains. By studying the supply chains of Domori and Belyzium, this study intends to provide an increased understanding of supply chains in which there is traceability. Specifically, this study aims at analysing the objectives for why there is traceability in Domori and Belyzium’s supply chains and to determine the key organisational characteristics of these chains. The study uses a qualitative research strategy and a multiple case study research design. Its purpose is to explore and it aims at creating new theory from the collected data. Data was primarily collected from interviews, observations and documents. The study concludes that the most important objective for why there is traceability in the studied chains is to allow Domori and Belyzium to take quality improvement measures at their cocoa suppliers. Additionally, several key organisational characteristics of the supply chains were identified. Domori and Belyzium purchase cocoa directly from cocoa producers, without going through traders or cocoa processors. By doing so, they have control over processes that affect the quality of the final product and are able to exchange information with cocoa producers. Furthermore, Domori and Belyzium’s supply chains are characterized by high supply chain transparency, partnerships relationships between chocolate producers and cocoa suppliers and defect preventive approaches to quality – all which are positively related to achieving sustainability in supply chains.
Keywords: Annan samhällsvetenskap; Other Social Sciences